HIV/AIDS: Current Updates on the Disease, Treatment and Prevention - Gupta, Praveen Kumar (Proc Natl Acad Sci India Sect B Biol Sci, 2021)
CCR5-delta 32 homozygous stem cell transplantation for HIV-infected individuals is being treated as a milestone in the global AIDS epidemic. Since 2008, when the second Berlin patient was cured from HIV after undergoing transplantation from a donor with delta-32 mutation, scientists are aiming for a long-term cure for the wider population. In 2019, a London patient became the second person to be free of HIV and came off the antiretroviral drugs completely. CCR5 gene is now being treated as a viable target for HIV treatment. It can be used in the treatment of HIV either through administration of drugs that bind to CCR5 and stop the receptor from working or through gene therapy to alter the CCR5 gene using CRISPR/Cas9 and prevent protein production. This review article aims to identify the obstacles and the need to overcome them in order to bridge the gap between current research and future potential cures for HIV.